2019
DOI: 10.1186/s12909-019-1727-3
|View full text |Cite
|
Sign up to set email alerts
|

Training to reduce LGBTQ-related bias among medical, nursing, and dental students and providers: a systematic review

Abstract: Background Lesbian, gay, bisexual, transgender and questioning (LGBTQ) individuals experience higher rates of health disparities. These disparities may be driven, in part, by biases of medical providers encountered in health care settings. Little is known about how medical, nursing, or dental students are trained to identify and reduce the effects of their own biases toward LGBTQ individuals. Therefore, a systematic review was conducted to determine the effectiveness of programs to reduce health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
179
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(196 citation statements)
references
References 78 publications
4
179
0
13
Order By: Relevance
“…Training programs that provide exposure to LGBT patients can increase medical students' comfort levels in caring for this population [6]. Likewise, LGBT education programs can increase knowledge [6] and confidence in clinical assessments [7] of LGBT people among medical students. Over the past decade, many medical schools have made efforts to include LGBT-specific healthcare topics in their curricula.…”
Section: Introductionmentioning
confidence: 99%
“…Training programs that provide exposure to LGBT patients can increase medical students' comfort levels in caring for this population [6]. Likewise, LGBT education programs can increase knowledge [6] and confidence in clinical assessments [7] of LGBT people among medical students. Over the past decade, many medical schools have made efforts to include LGBT-specific healthcare topics in their curricula.…”
Section: Introductionmentioning
confidence: 99%
“…LGBT curricular education are important factors for healthcare professional students' cultural competency. This finding is akin to the few studies that have shown that curricular education can be effective in ameliorating LGBT-specific attitudes, preparedness, and knowledge among dental, [18] medical, [7,8] and pharmacy [19,20] students. As such, both local and national educational initiatives should advocate for these experiential variables.…”
Section: Plos Onementioning
confidence: 67%
“…To our knowledge, this study presents the first multicenter, multidisciplinary assessment of multiple healthcare professional students' levels of LGBT cultural competency. Over the past decade, there has been momentum supported by evidence [6,7] to increase LGBT healthcare education. Obedin-Maliver et al's [15] and Hillenburg et al's [16] comprehensive studies of 176 medical schools and 32 dental schools, respectively, revealed the sparse LGBT education that students across the nation receive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LGBT+ (Loira et al, 2019;Braun, Ramirez, Zahner, Gillis-buck, Sheriff, & Ferrone, 2017;Morris et al, 2019;Zelin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%